Solar Powered Flood Detection Device: With Datalogging and Global Positioning System (GPS) For Traffic Diversion - Hashim, Muhammad Alif; A Majid, Huda; Saparudin, Faiz Asraf; Ab Ghafar, Aimi Syamimi (Progress in Engineering Application and Technology, 2020)
This paper discusses the development of sensor node circuit design for the use of Real Time Flood Detection System for Traffic Diversion Assistance in Urban City. The step of designing the sensor circuit and the technical explanation can be found in further section of this paper. The experiment is conducted to evaluate the performance of each sensors and their durability and reliability. The step of designing the solar power system and the method used to develop the charge controller is explained in detail in this paper. The experiment is conducted to evaluate the designed system performance. The cost of the development of device is presented.